2008
DOI: 10.1111/j.1462-5822.2008.01130.x
|View full text |Cite
|
Sign up to set email alerts
|

Rho1 has distinct functions in morphogenesis, cell wall biosynthesis and virulence of Fusarium oxysporum

Abstract: SummaryRho-type GTPases regulate polarized growth in yeast by reorganization of the actin cytoskeleton and through signalling pathways that control the expression of cell wall biosynthetic genes. We report the cloning and functional analysis of rho1 from Fusarium oxysporum, a soilborne fungal pathogen causing vascular wilt on plants and opportunistic infections in humans. F. oxysporum strains carrying either a Drho1 loss-of-function mutation or a rho1 G14V gain-offunction allele were viable, but displayed a se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
68
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(71 citation statements)
references
References 58 publications
3
68
0
Order By: Relevance
“…In yeast and F. oxysporum, Rho1 has been suspected to play a crucial role in modulating the activity of chitin synthase, a core component of the cell wall biosynthesis machinery (30,42). A rho1-null F. oxysporum is incapable of maintaining hyphal growth on solid medium (30). In mammalian systems, Rho/Rac-GTPases regulate lamellae formation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In yeast and F. oxysporum, Rho1 has been suspected to play a crucial role in modulating the activity of chitin synthase, a core component of the cell wall biosynthesis machinery (30,42). A rho1-null F. oxysporum is incapable of maintaining hyphal growth on solid medium (30). In mammalian systems, Rho/Rac-GTPases regulate lamellae formation.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Rac1 has been shown to regulate cell polarity, while Cdc42 regulates cytokinesis in U. maydis (29). In yeast and F. oxysporum, Rho1 has been suspected to play a crucial role in modulating the activity of chitin synthase, a core component of the cell wall biosynthesis machinery (30,42). A rho1-null F. oxysporum is incapable of maintaining hyphal growth on solid medium (30).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to S. cerevisiae, Rho1 is required for cell viability in C. albicans (Smith et al, 2002). In contrast, rho1 knockout mutants of the soilborne pathogen Fusarium oxysporum were viable and showed drastically reduced virulence on plants, but retained full virulence on immunodepressed mice (Martinez-Rocha et al, 2008). Both Rom1 and 2, as well as Rho1, are widely conserved in fungi, with a single orthologue of the two GEFs present in almost all species studied.…”
Section: The Mpk1 Cell Integrity Pathwaymentioning
confidence: 99%
“…In addition, the identification of the small GTPase Rho1p as being localized on peroxisomes by interaction of the peroxisomal membrane protein Pex25p again indicates a link of peroxisomes with the secretory machinery 61 , since Rho1p is known to play a role in actin reorganization and membrane dynamics 62,63 . In yeast, polarized growth is regulated by Rho1p 64 , and also in fungal systems the link between Rho1 and polarized growth has been confirmed 65 in the filamentous fungus A. niger, polarized growth is linked to secretion of proteins 66 . More recent papers also very clearly showed that peroxisomes originate from the endoplasmic reticulum 60,67,[68][69][70] .…”
Section: Engineering Membrane Trafficking As a Novel Conceptmentioning
confidence: 99%